2022
DOI: 10.3390/su141711010
|View full text |Cite
|
Sign up to set email alerts
|

A Car-Following Model for Mixed Traffic Flows in Intelligent Connected Vehicle Environment Considering Driver Response Characteristics

Abstract: Autonomous driving technology and vehicle-to-vehicle communication technology make the hybrid driving of connected and automated vehicles (CAVs) and regular vehicles (RVs) a long-existing phenomenon in the coming future. Among the existing studies, IDM models are mostly used to study the performance of homogeneous traffic flow. To explore the stability of mixed traffic flow, an extended intelligent driver model (IDM) based car-following model was proposed for mixed traffic flow (MTF) with both CAVs and RVs, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Autonomous driving technology and V2V communication technology will induce the long-term mixed traffic flow of CAVs and regular vehicles in the future [25,26]. There are many theoretical studies on mixed traffic flow.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Autonomous driving technology and V2V communication technology will induce the long-term mixed traffic flow of CAVs and regular vehicles in the future [25,26]. There are many theoretical studies on mixed traffic flow.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Dolayısıyla, sınır şartı olarak cidarda kaymama sınır şartı geçerlidir ve bu sınır şartı altında Navier-Stokes denklemi kullanılarak akışın çözümü yapılır. Yüzeye yakın yerdeki akışın sıcaklığı yüzey sıcaklığına eşittir [1,3,6,[16][17][18]. Knudsen sayısının 10-1 ile 10 arasında olduğu bölgeye geçiş akışı bölgesi (transition flow region) ismi verilir.…”
Section: Akış çEşitleriunclassified
“…As the field of autonomous driving and wireless communication technology matures, more and more attention has been paid to the research and development of connected automated vehicles [1][2][3][4]. Relevant research [1] shows that in the next 5 years around 10% of vehicles on the road will be CAVs, and in the next 30 years the proportion will rise to 75%.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], it is shown that the driver's psycho-physiological characteristics are the factors that affect driver response time. (2) In terms of secondary task driving behavior, the researchers in [15] found that the execution of secondary task driving behavior would reduce driver response time to the front vehicle, while attention to the road was more concentrated.…”
Section: Introductionmentioning
confidence: 99%